إسهام القطاع السياحي في دعم مؤشرات الأقتصاد الوطني - دراسة تحليلية لحصيلة القطاع السياحي - - طويطي, مصطفى; مجدوب, خيرة (Université de M'sila, 2017)
Algeria is one of the important tourist poles With all its elements supportive of sustainable tourism, this view of the tourist potential that distinguishes them from many countries, especially the African and Arab level. Being characterized by a coastal strip extending along the 1200 km overlooking the Mediterranean Sea, Besides possessing stunning diversity of climatic zones and allow the continuation of tourism throughout the year, Add to that distinctiveness desert ranked of the most beautiful deserts of the world, the multiplicity of traditions and diversity of effects earned it biologically unique, but despite this enormous tourism potential available to Algeria is that the status of the tourism sector known significant weakness compared with neighboring countries such as Tunisia and Morocco, and even Arab countries such as Egypt and Jordan, which calls for the need to take action necessary for the advancement of this sector in particular, and that the flow of Algerian tourists about various countries reached 3,638,140 tourists for 2015, which far exceeds the flow of tourists to Algeria, but did not exceed even half (1.709.994 tourists) for the same year.